Design of a wave energy converter system for the Colombian Pacific Ocean (2020)
This paper details the mechanical design of a wave power generation system comprising a buoy that houses a set of mechanical devices and a linear generator. The system proposed transforms the heaving movement of the buoy in a rotational movement of the arm that houses the linear generator. Firstly, the conceptual design and the operation of the system is exposed. Secondly, the conditions of the waves in the zone of interest are presented; in this case, the device was designed to work in the Colombian Pacific Ocean. Afterwards, the dynamic model of the buoy and the linear generator are deduced starting off the movement laws. To solve the resulting equation, Ansys Aqwa® numerical software is used to know the behavior of the device under the features of the swell conditions. Finally, the simulation results under real conditions are presented and compared to the response under incident regular wave. To determine the amount of electric power generated, a calculus routine in Matlab® is implemented. Throughout the numerical code, the electric power generated is calculated at each time step, and the average electric power is solved subsequently. It was found that under regular and irregular swell conditions the amount of electricity produced was 1.17 and 0.5 kW, respectively. In this regard, the device proposed here is an interesting option for populations inhabiting near coastlines far from existing electricity grids